KEPUTUSAN PEMBELIAN ONLINE MELALUI SITUS JUAL BELI LAZADA TERHADAP PERILAKU KONSUMTIF MASYARAKAT PONTIANAK KALIMANTAN BARAT - Dina Octaviani; Viren Pratama (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This study aims to determine the relationship between purchasing decisions, products, prices, services, risks to consumer behavior. The method used is a quantitative approach using multiple linear regression analysis, supported by statistical tests, using the SPSS version 20. Partial testing of the purchase decision coefficient there is a relationship to consumptive behavior of 1,721 or 17.21%. The product coefficient is related to the consumptive behavior of 1,962 or 19.62%. The price coefficient is related to the consumptive behavior of 1.188 or 11.88%. The coefficient of service there is a relationship to consumptive behavior of -0.705 or -07.05%. The risk coefficient is related to consumptive behavior of 3,811 or 38.11%. Partially there is a relationship between purchasing decisions, products, prices, services and risks to consumptive behavior.